Microbiology : an evolving science - Slonczewski, Joan; Foster, John W. (John Wade); Zinser, Erik R. (W.W. Norton & Company, 2024)
"Microbiology: An Evolving Science is an undergraduate majors microbiology textbook, written to convey exciting research in a rapidly evolving field while also motivating students to learn the fundamentals amid an overwhelming amount of information. Engaging examples, abundant eye-catching figures, updated genetics and genomics content by new coauthor Erik Zinser, all help the reader understand the complex microbial world"--